Political Communication and the Right to Information: Fulfilling the Public's Right to Information on Elections in the 2024 Bali Regional Elections - Ni Wayan Widhiasthini; Made Srinitha Millinia Utami; Nyoman Sri Subawa; Nyoman Sridiva Dian Prabarini (Politicon : Jurnal Ilmu Politik, 2026)
This study aims to critically analyze how political communication practices carried out by the General Election Commission (KPU), regional head candidates, and the mass media contribute to fulfilling the public's right to electoral information in the context of local democracy in Bali. Using a qualitative approach with an exploratory case study design, this study combines data from in-depth interviews, focus group discussions (FGDs), and digital content analysis to examine the relationship between transparency, political communication, and public participation in the 2024 Bali Regional Elections. The results show that the Bali KPU has made efforts to fulfill the principle of the right to information through the provision of digital channels, the publication of electoral data, and cooperation with local media. However, the communication patterns that have been established are still one-way and lack deliberation. Meanwhile, candidates' political communication strategies are dominated by image-based and symbolic politics approaches that emphasize image and emotional slogans over policy program substance, creating information asymmetry between candidates and voters. Local media and digital spaces also do not fully serve as vehicles for political education, but rather as arenas for electoral promotion. This study confirms the gap between formal and substantive transparency in local political communication practices. Therefore, the fulfillment of the public's right to electoral information needs to be realized through more educational, participatory, and interactive political communication. This study contributes to the development of academic discourse on information politics and public accountability and provides practical implications for strengthening transparent and integrity-based local democracy